Structural Efficiency of Steel Stiffening Deck Systems in Suspension Bridges Due to Gravity Loads - Hussein, Ahmed Gasim M.; Mohamed, Mohamed Faisal F. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
In this paper, suspended stiffened decks in suspension bridges are considered. Three steel deck-stiffening systems are compared structurally; the plate girder, the box girder and the stiffening truss. A three-span continuous suspension bridge model is considered. Analysis is made by the second order non-linear deflection theory in its linearized form. Developed software is used for the analysis to determine the induced tension in the cable, moments, shears and deflections of the girders for any general live load case. AASHTO criteria for steel girders are adopted. AASHTO highway live loads -HL 93- are applied to Khartoum-Tuti Suspension Bridge in Khartoum, Sudan for each type of the stiffening systems. Ten load cases are considered and discussed. Results have shown that the most efficient type to resist gravity loads is the stiffening truss, followed by the box girder and last is the plate girder